Design Perception According to Gender in Landscape Architecture - Sertaç Güngör; Ceren Akyüz (Turkish Journal of Agriculture: Food Science and Technology)
The primary purpose of this study is whether gender, which is a culturally and socially defined concept, affects the perception of landscape architecture. Secondly, it is aimed to determine the preferences of the designs created in landscape architecture studies according to gender and to guide the questionnaire results in the creation of areas suitable for user requests during the design phase. The concept of admiration, preference and accompanying beauty, the effect it has on people according to gender, show various differences. These differences lead to perceptual selectivity in terms of colour, texture, form, functional and aesthetically depending on gender. Therefore, tastes and preferences are not expected to be a single judgment but to vary. Since there is no possibility of face-to-face surveys due to the current Covid-19 outbreak, online surveys were conducted on 220 people who can be reached in professional groups on social media. In the content of the questionnaire, the landscape design criteria and design elements were handled, and the visuals and preferences selected for each definition were directed to the participants as questions. According to the evaluated results, differences occurred in perceptual preferences depending on gender. In addition to the fact that there was no statistically significant difference between the preferences of women and men in terms of design criteria and elements, the preferences of both groups were combined in natural or close to nature forms. Considering the proportions, there was no obvious difference in design perceptions preferred by gender.